Compensation and Work Facilities as Determinants of Lecturer Performance: The Mediating Role of Work Motivation - Gifari Iman Nugroho; I Made Dauh Wijana; Ni Made Dwi Puspitawati; Ni Putu Cempaka Dharmadewi Atmaja (Journal of The Community Development in Asia, 2025)
This study is motivated by the declining performance of lecturers at the Denpasar Islamic Religious College, particularly reflected in limited research activities. The purpose is to examine the influence of compensation and work facilities on lecturer performance, with work motivation as a mediating variable. A quantitative approach was applied, collecting data through questionnaires from 30 permanent lecturers using the census technique. Data were analyzed with Partial Least Squares (PLS), a structural equation modeling (SEM) method for assessing direct and indirect relationships. The findings show that compensation (p = 0.736; t = 0.337) and work facilities (p = 0.995; t = 0.007) have no significant direct effect on lecturer performance. However, compensation (p = 0.000; t = 4.141) and work facilities (p = 0.027; t = 2.128) significantly influence work motivation, which in turn positively impacts performance (p = 0.030; t = 3.009). Mediation analysis confirms that work motivation fully mediates the relationship between compensation, work facilities, and performance. The study concludes that strengthening lecturer motivation is essential for enhancing performance, emphasizing the importance of better compensation systems and adequate work facilities.